Language and Culture with Special Reference to Japanese - Kampmark, Karl Jurgen (Journal of Modern Languages, 2017)
This article deals with some of the issues which come up whenever we try to understand the position of man in relation to himself, language and society. The focus of the paper is on speech and whether or not the speech-act is deterÂmined by factors external to the individual speaker. It is regarded as a truism that language is what primarily distinguishes man from other life-forms and that 'between the clearest animal call of love or warÂning or anger, and man's least trivial word there lies a whole day of Creation', as Langer (1967) mentions.